The Effect of CLA-Rich Isomerized Poppy Seed Oil on the Fat Level and Fatty Acid Profile of Cow and Sheep Milk - Robert Bodkowski; Katarzyna Czyż; Anna Wyrostek; Paulina Cholewińska; Ewa Sokoła-Wysoczańska; Roman Niedziółka (Animals, 2020)
The aim of the study was to examine the effect of dietary supplementation of isomerized poppy seed oil (IPO) enriched with conjugated dienes of linoleic acid (CLA) on cow and sheep milk parameters (fat content, fatty acid profile, Δ9-desaturase index, and atherogenic index). The process of poppy seed oil alkaline isomerization caused the formation of CLA isomers with cis-9,trans-11, trans-10,cis-12, and cis-11,trans-13 configurations in the amounts of 31.2%, 27.6%, and 4.1% of total fatty acids (FAs), respectively. Animal experiments were conducted on 16 Polish Holstein Friesian cows (control (CTRL) and experimental (EXP), n = 8/group) and 20 East Friesian Sheep (CTRL and EXP, n = 10/group). For four weeks, animals from EXP groups received the addition of IPO in the amount of 1% of dry matter. Milk was collected three times: on days 7, 14, and 30. Diet supplementation with IPO decrease milk fat content (p < 0.01). Milk fat from EXP groups had higher levels of polyunsaturated fatty acids, including FAs with beneficial biological properties, that is, CLA and TVA (p < 0.01), and lower levels of saturated fatty acids, particularly short- (p < 0.01) and medium-chain FAs (p < 0.05). The addition of IPO led to a decrease in the atherogenic index.